A community-based, cross-sectional study to assess interactions between income, nutritional status and enteric parasitism in two Brazilian cities: are we moving positively towards 2030? - Deiviane A. Calegar; Polyanna A. Bacelar; Kerla J. L. Monteiro; Jessica P. dos Santos; Andressa B. Gonçalves; Márcio N. Boia; Lauren H. Jaeger; Beatriz Coronato-Nunes; Filipe A. Carvalho-Costa (BMC, 2021)
Abstract Background This study assessed the interactions between income, nutritional status and intestinal parasitism in children in Brazil. Methods A cross-sectional study (n = 421 children aged 1 to 14 years living in the states of Piauí (rural communities in the city of Teresina) and Rio de Janeiro (rural and periurban communities in the city of Cachoeiras de Macacu) was performed in order to obtain income and anthropometric data, as well as fecal samples for parasitological analyses through the Ritchie technique. Results Children infected with Ascaris lumbricoides had significantly lower means of height-for-age z scores (− 1.36 ± 0.75 vs. − 0.11 ± 1.02; p < 0.001), weight-for-age z scores (− 1.23 ± 0.74 vs. 0.09 ± 1.15; p = 0.001), and weight-for-height z scores (− 0.68 ± 0.44 vs. 0.23 ± 1.25; p = 0.006) when compared with uninfected children. Infection with hookworm was also associated with lower means of height-for-age z scores (− 1.08 ± 1.17 vs. − 0.12 ± 1.02; p = 0.015) and weight-for-age z scores (− 1.03 ± 1.13 vs. 0.08 ± 1.15; p = 0.012). Children infected with Entamoeba coli presented significantly lower means of height-for-age z scores (− 0.54 ± 1.02 vs. − 0.09 ± 1.02; p = 0.005) and weight-for-age z scores (− 0.44 ± 1.15 vs. 0.12 ± 1.15; p = 0.002). The multivariate multiple linear regression analysis showed that height-for-age z scores are independently influenced by monthly per capita family income (β = 0.145; p = 0.003), female gender (β = 0.117; p = 0.015), and infections with A. lumbricoides (β = − 0.141; p = 0.006) and Entamoeba coli (β = − 0.100; p = 0.043). Weight-for-age z scores are influenced by monthly per capita family income (β = 0.175; p < 0.001), female gender (β = 0.123; p = 0.010), and infections with A. lumbricoides (β = − 0.127; p = 0.012), and Entamoeba coli (β = − 0.101; p = 0.039). Monthly per capita family income (β = 0.102; p = 0.039) and female gender (β = 0.134; p = 0.007) positively influences mid upper arm circumpherence. Conclusions Intestinal parasitism and low family income negatively influence the physical development of children in low-income communities in different Brazilian regions.